The commonwealth block, Melbourne : a historical archeaology - Murray, Tim, 1955- (Studies in Australasian historical archaeology, 2019)
This groundbreaking book reports on almost three decades of excavations conducted on the Commonwealth Block - the area of central Melbourne bordered by Little Lonsdale, Lonsdale, Exhibition and Spring streets.